THE INFLUENCE OF GOOD CORPORATE GOVERNANCE PRINCIPLES, INTERNAL CONTROL SYSTEMS, AND ORGANIZATIONAL COMMITMENT ON UPT PERFORMANCE WITH HUMAN RESOURCES COMPETENCE AS A MODERATING VARIABLE IN IMPLEMENTING UNITS TECHNICAL DIRECTOR GENERAL OF RESOURCES AND - Nurapnita Rozalia Inda; Chablullah Wibisono; Irfan; Robin; Muamar Khaddafi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
UPT performance is work performance achieved by UPT in realizing the activity or program targets that have been set at the beginning effectively and efficiently. This study aims to determine the effect of good corporate governance, internal control systems, organizational commitment on UPT performance with human resource competence as a moderating variable in Technical Implementation Units of the Directorate General of Resources and Equipment of Post and Information Technology throughout Indonesia. The population in this study were 35 UPT Directorate General of Resources and Equipment of Post and Information Technology throughout Indonesia. A sample of 140 respondents who are activity managers in each UPT. Sources of data used are primary data and data collection techniques through questionnaires. Data were analyzed using Partial Least Square (PLS). The results of the study show that good corporate governance, internal control systems, organizational commitment, and human resource competence have a significant positive effect on UPT performance. Human resource competence is only able to moderate the effect of organizational commitment on UPT performance, but is unable to moderate the effect of good corporate governance and internal control systems on UPT performance.